The protagonism of deaf person: Education as a means of social ascent (Research, Society and Development, 2021)
To be the protagonist is to promote something memorable in your social group and/or in your culture. Historically, the protagonism wasn't delegated to people of inferior classes or "marginalized" social groups. However, history is mutable, which means that new opportunities of social ascent always emerge, above all, by the means of education. The history of a deaf person is an example of it since he passed through some phases, whereas sometimes they were considered cursed, other times deities, then, finally, rightful citizens. In this context, the present research was developed to understand the preamble of the history of the deaf person and his possibility of protagonism in the society by the means of education. This work was built through a bibliographic approach, with which we sought to show some of the problematic of the insertion of deaf people into higher education, that is, into the public universities of the country. This way, this study enables a range of possibilities of social interpretation when we put into the center the protagonism of the deaf person.